O Chile contemporâneo na historiografia política de Tomás Moulian - Martins, Camila Savegnago [UNESP] (2014)
This dissertation intents to discuss the contribution of the Chilean intellectual and social scientist – Tomás Moulian, on the building of the political historiography of contemporary Chile, using its main works and studies about the country. Therefore, it is fundamental the understanding of the politic-cultural formation of the Latin-American intellectual, as well as other elements that constitutes it: sociability networks, exile, political acting, among others. Not less important is the investigation of thoughts influences received by Moulian over his trajectory. It’s a reflection on how important political processes, that occurred on the second half of the 20th century in Chile, as the ascension and overthrow of Salvador Allende and the Popular Unity of the power (1970-1973), the military government of Augusto Pinochet (1973-1989), the transition to democracy and even the after-concertación, are seen, related and interpreted by the author. From this thorough analysis, considering also different actors that compound and still are part of the political spectrum of Chile, it’s going to be possible to establish a dialog with one of the keys of interpretation of the author, called “transformismo”, that, according to Moulian, constitutes one of the important elements in comprehending contemporary Chile’s transformation. Hence, the aim of the research is also to approach new elements existents on the intellectual Tomás Moulian approaches perspectives: questions involving the conception of a new socialism to Chile on the 21th century, the deepening of democracy and the diverse elements that constitutes it, that also are part of contemporary Chile